Flufenamic acid decreases neuronal excitability through modulation of voltage-gated sodium channel gating - Yau, Hau-Jie (Blackwell Science Inc, 2010)
The electrophysiological phenotype of individual neurons critically depends on the biophysical properties of the voltage-gated channels they express. Differences in sodium channel gating are instrumental in determining the different firing phenotypes of pyramidal cells and interneurons; moreover, sodium channel modulation represents an important mechanism of action for many widely used CNS drugs. Flufenamic acid (FFA) is a non-steroidal anti-inflammatory drug that has been long used as a blocker of calcium-dependent cationic conductances. Here we show that FFA inhibits voltage-gated sodium currents in hippocampal pyramidal neurons; this effect is dose-dependent with IC(50) = 189 μm. We used whole-cell and nucleated patch recordings to investigate the mechanisms of FFA modulation of TTX-sensitive voltage-gated sodium current. Our data show that flufenamic acid slows down the inactivation process of the sodium current, while shifting the inactivation curve ∼10 mV toward more hyperpolarized potentials. The recovery from inactivation is also affected in a voltage-dependent way, resulting in slower recovery at hyperpolarized potentials. Recordings from acute slices demonstrate that FFA reduces repetitive- and abolishes burst-firing in CA1 pyramidal neurons. A computational model based on our data was employed to better understand the mechanisms of FFA action. Simulation data support the idea that FFA acts via a novel mechanism by reducing the voltage dependence of the sodium channel fast inactivation rates. These effects of FFA suggest that it may be an effective anti-epileptic drug.